Методика оценки эффективности использования в системе электроснабжения полупроводниковых преобразователей постоянного напряжения - Поляков, Михаил Алексеевич; Ларионова, Татьяна Юрьевна (НТУ "ХПИ", 2016)
Разработана методика оценки эффективности использования силового полупроводникового преобразователя постоянного напряжения в системе электроснабжения. Методика включает выявление множества внешних факторов, влияющих на эффективность использования преобразователя; разработку модели оценки эффективности как функции внешних факторов; выбор варианта использования преобразователя; установление коэффициентов корреляции между значениями внешних факторов; определение значений КПД преобразователя; нахождение распределения КПД преобразователя. Применение предложенной методики проиллюстрировано на примере синхронного промежуточного вольтодобавочного преобразователя постоянного напряжения. Для этой цели выполнено статистическое моделирование преобразователя этого типа при стохастичном изменении входного напряжения.

Purpose. To specify efficiency evaluation of the DС-DC power semiconductor converter application in the power-supply system. Methodology. We have chosen application version of converter and then used the statistical modeling of DC-DC converter for its efficiency evaluation at varied input voltage according to proposed technique. We have compared the simulated result with the data presented in reference literature. Results. We have proposed the efficiency evaluation technique of converter application. Proposed technique includes detection of external factors influenced on the converter efficiency; development of efficiency evaluation models; selecting application version of converter; determination of the correlation coefficients between the values of external factors; definition of the converter efficiency; obtaining of the converter efficiency distribution. Originality. For the first time, we have developed the evaluation technique of converter efficiency corrected for application version of converter. Practical value. Presented in the study results could be useful for specialists in semiconductor equipment, electrical facilities and systems.
Efficiency evaluation technique of the semiconductor DC-DC converter application in the power-supply system
Keywords: полупроводниковый преобразователь; статистическое моделирование; оценка эффективности; КПД преобразователя; semiconductor converter; efficiency of converter application; statistical modeling; evaluation of the effectiveness; converter efficiency